SEM - PLS in the WebQual 4.0 Method for Enhancing the Quality of Online Tutorial Learning Applications at Open Universities - Suwardika, Gede; Suniantara, I Ketut Putu; Masakazu, Kadek (Universitas Pendidikan Ganesha, 2023)
Universitas Terbuka (UT, literally Open University) organizes distance learning through the Online Tutorial (Tuton) service. Tuton is an internet-based tutorial service that can be accessed via the site http://elearning.ut.ac.id by all UT students, including UPBJJ UT Denpasar students. Analysis of the quality of UPBJJ UT Denpasar student tutoring services has never been carried out before. Based on these problems, this research aims to analyze and measure the quality of Tuton application services using WebQual 4.0 dimensions, which are moderated by gender and age variables. This research uses a quantitative method approach to student satisfaction data from the UT UPBJJ Denpasar Management Study Program, who have used the Tuton application for more than three semesters. Data analysis techniques using the SEM–PLS method. Based on the results of the analysis, it was found that there was a positive influence between the usability variable, the service interaction quality variable, and the Information Quality variable on the user satisfaction variable. The gender moderating variable can act as pure moderation on the service interaction quality and Information Quality variables. Meanwhile, the age variable is a potential moderator of the three variables. From these results, it can be concluded that the service quality of the Tuton application shows a robust model on the Webqual Method indicators for user satisfaction variables, and this application is beneficial and in accordance with student needs. The learning support aspects still need to be improved, especially the speed of response time and the accuracy of the tutorial services provided by tutors.